Seroprevalence of HIV/AIDS and HIV risk factors among prison inmates in Ogun State, Nigeria. (2012)
Background: Prevalence of HIV in Ogun State has remained low since the history of HIV infection in Nigeria. Nevertheless, there have been evidences of higher HIV prevalence in some populations within the state but studies among inmates in the state have not been comprehensive. In the present study, we report data to bridge this gap in knowledge. Methods: A total of 340 inmates comprising of 101 and 239 consenting inmates from the Sagamu and the Abeokuta prisons (respectively) participated in this study. Trained personnels interviewed consented inmates using structured questionnaires. Blood samples collected from all participants were tested for HIV antibodies on a one-on-one basis using Determine® and Starpac® test kits (for the HIV test and the confirmatory test respectively). Descriptive statistics, chi-square test and the logistic regressions were used to analyze the data using SPSS version 13. Results: We found that 10.6% of the inmates had been involved in same sex. Although the overall HIV prevalence among inmates in this study was found to be 2.4%, HIV prevalence was 2.6% and 2.1% among inmates who don’t use and those who use condom during casual sex respectively. The odds of not using condom and their respective 95% confidence interval (CI) were found to be 2.03 (1.19–3.46) and 3.68 (1.17–11.57) among inmates in the 31–60 age category and among inmates who were students respectively. Conclusions: The presence of same sex practices among the inmates is a potential precursor for future explosion of HIV infection in these prisons, particularly that some of them were HIV positive.